209 Case report of a COVID 19 patient presenting with acute abdomen and diagnosed to have high grade serous ovarian carcinoma. (13th November 2020) - Basha Mohamed, M; Arora, R
Abstract : Introduction: Acute abdominal pain is a rare presentation of the coronavirus disease 2019 (COVID-19). The effect on the gynaecological tract is not well known. We present a COVID-19 case admitted with abdominal pain and diagnosed to have ovarian cancer. Methods: Clinical details were retrieved using electronic health record system. COVID-19 PCR swab test was performed using the Real-time SARS-CoV-2 Assay. Hematoxylin-Eosin, Martius Scarlett Blue stains, C3 and C4d immunohistochemical stains and RNAscope test were performed on the tube, ovary and omental tissue. Results: A 46 yr old known asthmatic presented to the emergency department with acute abdominal pain. On examination, she was febrile with a tender abdomen. Chest X-Ray showed bilateral patchy lower zone opacification. Abdominal ultrasound scan revealed a 151 × 148 × 55 mm pelvic mass. COVID-19 swab test requested just prior to the surgery came back positive. She had increased C-reactive protein with normal blood coagulation parameters. She underwent emergency unilateral salpingo-oopherectomy with omentectomy. Pathology revealed a high grade serous ovarian adenocarcinoma. Immunohistochemistry showed a linear pattern of C4d complement localized to omental capillary endothelial cells. C3 stain was negative. Martius Scarlett Blue stain did not show microthrombi. RNAscope failed to reveal coronavirus in the tissue. Conclusion: Our case contributes to the knowledge of atypical Covid-19 presentations. Complement split product C4d is a known pathological marker of antibody mediated rejection. While the presentation of ovarian cancer as acute abdomen could be co-incidental, C4d complement deposition in our case may suggest its role in COVID 19 pathogenesis.